2021
DOI: 10.1038/s41598-021-96210-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solid waste collection using RSM approach, and strategies delivering sustainable development goals (SDG’s) in Jeddah, Saudi Arabia

Abstract: The rapid industrial development, high population growth, and rapid urbanization of Saudi Arabia have led to increased pollution and waste levels. Every day, solid waste disposal for governments and local authorities becomes a significant challenge. Saudi Arabia produces over 15 million tonnes of solid waste annually, with a population of around 29 million. The waste production per person is estimated at between 1.5 and 1.8 kg per day per person. About 75% of the population in urban areas is concentrated, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Y denotes response (adsorption of Cr (VI), %); b 0 is the intercept value; b i ( i = 1,2,3,…,n) signifies the first model quantities for X i ; b ii signifies the quadratic coefficients of X i ; b ij are the correlation factors for X i X j ; and ɛ is the random error. Design-Expert software 10.0.1 (Stat-Ease Inc., Minneapolis, MN, USA) was used for all numerical assessments, analysis of variance (ANOVA), and numerical optimization of the RSM model [ 27 ]. The independent variables and their three levels appear in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Y denotes response (adsorption of Cr (VI), %); b 0 is the intercept value; b i ( i = 1,2,3,…,n) signifies the first model quantities for X i ; b ii signifies the quadratic coefficients of X i ; b ij are the correlation factors for X i X j ; and ɛ is the random error. Design-Expert software 10.0.1 (Stat-Ease Inc., Minneapolis, MN, USA) was used for all numerical assessments, analysis of variance (ANOVA), and numerical optimization of the RSM model [ 27 ]. The independent variables and their three levels appear in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…If these waste items are classified, it will boost the recycling process, which will positively affect the economic boost of the country [38]. It will also provide a much greener environment for future generations to live in [39]. In short, failing to prioritize recycling can cause wastage of natural resources, and financial loss [40,41].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Midgley et al [56] and Radwan et al [57] suggested that incineration is one of viable option to deal with municipal solid waste generated in Saudi Arabia. The United Arab Emirates (UAE) government intends to build a few incineration plants in order to reduce the volume of MSW produced and to reduce the landfill spaces required for the disposal [58].…”
Section: Municipal Solid Waste Incineration Ash (Mswia)mentioning
confidence: 99%